2015
DOI: 10.1111/cns.12446
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Reflexes and Windup In Vitro: Effects of Analgesics and Anesthetics

Abstract: The spinal cord is the first relay center for nociceptive information. Following peripheral injury, the spinal cord sensitizes. A sign of spinal sensitization is the hyper-reflexia which develops shortly after injury and can be detected in the isolated spinal cord as a "memory of pain." In this context, it is easy to understand that many analgesic compounds target spinally located sites of action to attain analgesia. In vitro isolated spinal cord preparations have been used for a number of years, and experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…These channels are recognized as therapeutic targets for regulating neuronal excitability. [28,32] We suggest that peroxide-mediated enhancement of potassium M-currents can be a possible therapeutic approach to this end, and exploration of faradaic devices in excitable cell models and in vivo is a future goal. In this present work, using single-cell electrophysiology protocols, we found that the peroxide-delivery pixel devices unambiguously enhanced M-currents of peroxide-sensitive Kv7.2/7.3 ion channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These channels are recognized as therapeutic targets for regulating neuronal excitability. [28,32] We suggest that peroxide-mediated enhancement of potassium M-currents can be a possible therapeutic approach to this end, and exploration of faradaic devices in excitable cell models and in vivo is a future goal. In this present work, using single-cell electrophysiology protocols, we found that the peroxide-delivery pixel devices unambiguously enhanced M-currents of peroxide-sensitive Kv7.2/7.3 ion channels.…”
Section: Discussionmentioning
confidence: 99%
“…[26,30] Neuropathic pain, commonly observed in cancer patients, is a further condition that is being associated with impaired Kv7.2/7.3 function and hyperexcitability. [31][32][33] According to more recent work by Gamper et al physiological concentrations of H 2 O 2 can activate Kv7.2/7.3 and enhance M-currents, making it a potentially potent therapeutic with a desired anti-excitable effect/silencing effect. [23] For this reason, we have chosen this type of ion channel as a target for faradaic H 2 O 2 -based stimulation in this work.…”
Section: Introductionmentioning
confidence: 99%
“…IC also modulates pain through affecting middle cingulate cortex, periaqueductal gray, locus coeruleus, the nucleus accumbens, or raphe nucleus . The spinal cord, the first relay center for nociceptive processing, is worthy of exploring pain mechanism and effects of antinociceptive drugs . The detailed neural circuitry among these areas definitely needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Digital band-pass filtering of the original DC signal between 200 and 1200 kHz allowed us to generate an AC channel to collect fast spike-like events produced by the firing of action potentials in motor neurones (Rivera-Arconada et al, 2016). Events crossing an amplitude threshold were counted in a time window between 100 and 950 milliseconds from stimulus artifact and summated to obtain the total spike counts to each train of stimuli.…”
Section: Downloaded Frommentioning
confidence: 99%